Hubungan Latihan Taekwondo Dengan Tingkat Kebugaran Remaja Usia 12 - 15 Tahun - Putri, Fadma; , Umi Budi Rahayu, S.Fis., S.Pd., M.Kes (2016)
Background: Adolescence is a period of transition from childhood to adulthood. In adolescence period, someone will experience a puberty phase which can affect the pyhsical fitness. Physical fitness is the ability to customize the functions of the body toward activity. Physical fitness is very important for everyone including adolescence or teenager to develop their potential physical activity. To obtain a good physical fitness, adolescence should do physical exercise regularly, such as taekwondo training. Objective: To find out the relationship of regular taekwondo exercise toward the fitness level of adolescents at 12-15 years old. Methods: This study is an observational research with cross sectional approach. The design of the study is point time apporoach, in which all subject of the was study was only observed once. The measurements was done by using the fitness Tes Kesegaran Jasmani Indonesia (TKJI). The data were analyzed by using chi square test and using the cross tab in calculating the odds ratio. Results: There was a relationship between regular taekwondo exercise toward the fitness level of adolescents at 12-15 years. Based on the statistical tests of cross tab obtained p-value of 0.000. Conclusion: There is a relationship between regular taekwondo exercise toward the fitness level of adolescents at 12-15 years old. Keywords: Regular Exercise, Taekwondo, Fitness, TKJI, Adolescence, 12-15 Years Old.